Biokinetic Characterization and Activities of N2O-Reducing Bacteria in Response to Various Oxygen Levels - Suenaga, Toshikazu; Riya, Shohei; Hosomi, Masaaki; Terada, Akihiko (Frontiers in Microbiology, 2018)
Nitrous oxide (N2O)-reducing bacteria, which reduce N2O to nitrogen in the absence of oxygen, are phylogenetically spread throughout various taxa and have a potential role as N2O sinks in the environment. However, research on their physiological traits has been limited. In particular, their activities under microaerophilic and aerobic conditions, which severely inhibit N2O reduction, remain poorly understood. We used an O2 and N2O micro-respirometric system to compare the N2O reduction kinetics of four strains, i.e., two strains of an Azospira sp., harboring clade II type nosZ, and Pseudomonas stutzeri and Paracoccus denitrificans, harboring clade I type nosZ, in the presence and absence of oxygen. In the absence of oxygen, the highest N2O-reducing activity, Vm,N2O, was 5.80 ± 1.78 × 10−3 pmol/h/cell of Azospira sp. I13, and the highest and lowest half-saturation constants were 34.8 ± 10.2 µM for Pa. denitirificans and 0.866 ± 0.29 µM for Azospira sp. I09. Only Azospira sp. I09 showed N2O-reducing activity under microaerophilic conditions at oxygen concentrations below 110 µM, although the activity was low (10% of Vm,N2O). This trait is represented by the higher O2 inhibition coefficient than those of the other strains. The activation rates of N2O reductase, which describe the resilience of the N2O reduction activity after O2 exposure, differ for the two strains of Azospira sp. (0.319 ± 0.028 h−1 for strain I09 and 0.397 ± 0.064 h−1 for strain I13) and Ps. stutzeri (0.200 ± 0.013 h−1), suggesting that Azospira sp. has a potential for rapid recovery of N2O reduction and tolerance against O2 inhibition. These physiological characteristics of Azospira sp. can be of promise for mitigation of N2O emission in industrial applications.